A Report on H mode in Magnetic Pole Enhanced Inductively Coupled Nitrogen Plasmas. Issue 6 (26th February 2013) - Jan, F.; Khan, A. W.; Saeed, A.; Zakaullah, M.
Abstract The properties of low pressure magnetic pole enhanced, inductively coupled nitrogen plasma were studied by using electrical probe (Langmuir probe) under the conditions of RF powers in the range of 50‐220 W and pressures of 15‐75 mTorr. The electron energy probability function (EEPF) and electron density (ne) obtained from the RF compensated Langmuir probe was compared with the theoretical results. The theoretical fits of the EEPF shows that the shapes of EEPF are evolved from generalised distribution to Maxwellian distribution function. It was also observed that at a low power (50 W) the discharge remains in inductive (H‐mode) mode for all the pressures (15‐75 mTorr). At a higher pressure and relatively low RF power, the measured EEPF show a hole near 3eV of energy. The intensities of the emission lines at 337.1nm (Second Positive System) and 391.4 nm (First Negative System) due to C3Πu → B3Πg and B2 <![CDATA[ extstyle _u^+]]> <inline-graphic xlink:href="ark:/27927/pgg22f59gpp" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> → X2 <![CDATA[ extstyle _g^+]]> <inline-graphic xlink:href="ark:/27927/pgg22f59gn4" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> transitions respectively, closely follows the variation of ne with RF power and filling gas pressure. The stability of the H mode was also investigated using skin depth. Electron temperature and plasma potential indicate that the discharge at higher power (above 50 W) almost remain in H mode. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)